Plant bio-regulators for enhancing quality and storability of Carambola (Averrhoa carambola) fruits - HAZARIKA, T K; TARIANG, KERMIKI (The Indian Journal of Agricultural Sciences, 2019)
Plant bio-regulators are natural and safe phenolic compounds which exhibit a high potential in controlling postharvest losses of horticultural crops. They act as moisture and gas barriers, preserve colour, texture and moisture, enhance quality and extend the shelf life. The present investigation was conducted at Post-harvest laboratory of Department of Horticulture, Aromatic and Medicinal Plants, Mizoram University, Aizawl during 2016-17 to study the effect of plant bio-regulators in quality of carambola (Averrhoa carambola L.), fruits. Total 9 treatments comprising control and different concentrations of Gibberellic Acid, 1-Naphthalene Acetic Acid, 6-Benzylamino Purine, Salicylic Acid were evaluated. The treatments were compared within 16 days at an interval of 4 days. Among the 9 treatments, NAA 100 ppm showed superiority in different quality attributing characters like physiological loss in weight (PLW) (17.33%), fruit firmness (4.62), decay per cent (16.10%),TSS (13.73Â°Brix), ascorbic acid (8.82 mg/100 g), titratable acidity (0.527%), total sugars (9.97%), reducing sugar (6.37%), TSS: acid ratio (26.15), taste (8.57), appearance (5.79), and overall acceptability (6.70). The same treatment recorded maximum shelf life by maintaining the best quality parameters.